2013
DOI: 10.1371/journal.pone.0059229
|View full text |Cite
|
Sign up to set email alerts
|

Reactomes of Porcine Alveolar Macrophages Infected with Porcine Reproductive and Respiratory Syndrome Virus

Abstract: Porcine reproductive and respiratory syndrome (PRRS) has devastated pig industries worldwide for many years. It is caused by a small RNA virus (PRRSV), which targets almost exclusively pig monocytes or macrophages. In the present study, five SAGE (serial analysis of gene expression) libraries derived from 0 hour mock-infected and 6, 12, 16 and 24 hours PRRSV-infected porcine alveolar macrophages (PAMs) produced a total 643,255 sequenced tags with 91,807 unique tags. Differentially expressed (DE) tags were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…Such studies have shown that the expression levels of MX1 , USP , IFN-β , IL-10 and TNF-α are affected by PRRSV infection [18], [19]. Overall, these analyses suggest that PRRSV subverts host defenses by inhibiting the expression of pro-inflammatory cytokines [20][22] and stimulating weak production of IFN-α [reviewed in 23].…”
Section: Introductionmentioning
confidence: 87%
“…Such studies have shown that the expression levels of MX1 , USP , IFN-β , IL-10 and TNF-α are affected by PRRSV infection [18], [19]. Overall, these analyses suggest that PRRSV subverts host defenses by inhibiting the expression of pro-inflammatory cytokines [20][22] and stimulating weak production of IFN-α [reviewed in 23].…”
Section: Introductionmentioning
confidence: 87%
“…Since described in USA in 1987, porcine reproductive and respiratory syndrome (PRRS) has now been one of the most important diseases in pigs, leading to significant economic losses in swine industry worldwide (Albina, 1997;Pejsak et al, 1997;Rossow, 1998). In 2005, the annual costs of PRRS for the American swine industry were approximately 560 million dollars (Neumann et al, 2005), and recently, the estimated costs are increased to about $664 million per year in the United States (Jiang et al, 2013). In the past twenty-seven years, PRRS has emerged in almost all of the pig-producing countries (Bilodeau et al, 1991;Cho and Dee, 2006;Kuwahara et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The long tags or targets certainly make it easier and more accurate to assign them to genes/transcripts. In terms of data amount, a conventional SAGE analysis usually results in less than 20,000 tag reads per library [59]. However, a typical SAG-seq run (DGETP) can now provide many tag reads, ranging from 3 to 30 million reads.…”
Section: Whole Transcriptome Tag/target Sequencing With Restriction Dmentioning
confidence: 99%